Clinicopathological Outcome of Cervical Lymphadenopathy - Abu Hasim Abdul Aziz; Anand Shankar; Nandkishor Shinde; Javeriya Farheen; Afia Kauser (RGUHS Journal of Medical Sciences)
Background amp Objectives Cervical lymphadenopathy is assessed clinically radiologically and pathologically with accurate diagnosis being crucial for effective management. This study evaluates patients with cervical lymphadenitis clinically and pathologically to confirm the diagnosis assess clinical behavior and determine management outcomes.Methods This cross-sectional prospective study was conducted at a tertiary care center over two years. Patients over 10 years old with cervical lymphadenopathy persisting for more than three weeks were included. The collected data included age sex symptom duration constitutional symptoms and a history of tuberculosis TB contact. A thorough local and general physical examination was performed followed by a complete blood count CBC erythrocyte sedimentation rate ESR neck ultrasound fine-needle aspiration cytology FNAC and excisional biopsy. Treatment was initiated based on confirmed diagnoses.Results The study included 50 patients predominantly aged 31-40 years with a male-to-female ratio of 1.271. Fever was the most common symptom 42 followed by pain 26. Lymph nodes were firm in 42 patients 84 multiple in 26 52 and unilateral in 45 90. Clinically TB lymphadenitis was the most common diagnosis 62 followed by acute suppurative lymphadenitis 18 and malignant metastasis 6. FNAC identified TB lymphadenitis in 54 and acute suppurative lymphadenitis in 14. FNAC demonstrated a sensitivity of 71.05 and a specificity of 100 making it a highly reliable diagnostic tool.Conclusion Tubercular lymphadenitis acute suppurative lymphadenitis and malignancies were the most common causes of cervical lymphadenopathy in this study. FNAC proved to be a highly sensitive and specific investigation for early and accurate diagnosis.